Biodegradation of brassica haulms by white rot fungus Pleurotus eryngii - Singh, M. P.; Pandey, V. K.; Srivastava, A. K.; Viswakarma, S. K. (Cellular and Molecular Biology, 2011)
The white rot fungus P. eryngii was grown on chemically and hot water treated agrowaste Brassica haulms. The fungus degraded lignin, cellulose, hemicellulose and carbon content of both chemically as well as hot water treated waste and produced in turn the edible and nutritious fruiting body. The progressive breakdown of lignin, cellulose and hemicellulose was correlated with apparent increase in the activities of lignolytic, cellulolytic and hemicellulolytic enzymes. Lignin degraded at faster rate during the vegetative phase and at slower rate during reproductive phase whereas, cellulose and hemicellulose depleted slowly during vegetative phase and rapidly during reproductive phase. The carbon content of the agrowaste decreased while, the nitrogen content increased and the C/N ratio came closer during degradation of the waste. Hot water treated substrate supported better production of enzymatic activity and degraded more efficiently than chemically sterilized substrate. The total yield and biological efficiency of the mushroom was the maximum on the hot water treated substrates.